Dedusting filtering material with anti-condensation and self-cleaning performance and preparation method thereof
By forming a gradient-covered surface treatment layer on the surface of the dust removal filter material, the problem of insufficient anti-condensation and adhesion capabilities of existing materials in high humidity, high temperature or oil-containing environments is solved, and a higher level of waterproof, oil-proof and anti-fouling performance is achieved, extending service life and improving dust removal efficiency.
Patent Information
- Application Number
- CN202510278811.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-11
AI Technical Summary
It is difficult for existing dust removal filter materials to maintain their anti-condensation and anti-adhesion capabilities in high humidity, high temperature or oil-containing environments for a long time, resulting in the ‘paste bag’ phenomenon, affecting the operating efficiency and maintenance cost of the dust collector.
The filter felt prepared by a needle puncture process and a gradient-covered surface treatment layer is formed on its surface, including perfluoro and polyfluoroalkyl compounds with linear carbon atoms, organic fluorosilic modified acrylate compounds and ethoxy non-ionic fluorocarbon surfactants, and a dense protective layer is formed by spraying and drying shaping treatment.
It significantly improves the waterproof, oil-proof and anti-fouling properties of the filter material, extends its service life under complex working conditions, effectively suppresses the "bag paste" phenomenon, and improves the dust removal rate and circulation time.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter materials, and in particular to a dust removal filter material with anti-condensation and self-cleaning properties and a preparation method thereof. Background Art
[0002] Bag dust collectors have been widely used in coal-fired power plants, steel smelting, cement production, glass manufacturing and other industrial fields due to their efficient dust removal capabilities, simple structure and convenient maintenance methods. However, in actual operation, due to the complex and changeable working conditions, filter bags are often affected by moisture, oil mist, high temperature and other factors, resulting in the degradation of filter material performance or even failure. Among them, the "bag sticking" problem is particularly prominent and has become one of the main problems restricting the stable operation of bag dust collectors. The "bag sticking" phenomenon refers to the situation in which dust adheres to the dust-facing surface of the filter material or the internal fibers under high humidity conditions or flue gas conditions containing oily substances, blocking the pores of the filter material, causing a sharp drop in air permeability and a significant increase in equipment resistance. This not only directly affects the operating efficiency of the dust collector, but also increases energy consumption, shortens the life of the filter bag, and even causes system shutdown and high maintenance costs for frequent replacement of filter bags.
[0003] At present, the industry mainly adopts coating and impregnation treatment, adding chemical water and oil repellent, laminating treatment and other methods to solve the problem of "sticky bag". Although the above technologies have alleviated the problem of "sticky bag" to a certain extent, their effects are often limited by the use environment, especially in high temperature, high humidity or oily environment. With conventional treatment methods, the anti-condensation and anti-adhesion capabilities of existing filter bag materials are difficult to maintain for a long time. After feedback from field applications and laboratory high temperature tests, it is found that the waterproof and oil-proof grades are prone to failure at a certain temperature. Therefore, there is an urgent need for a new type of filter material that has both anti-condensation, self-cleaning ability and durable oil-proof performance to meet the use requirements under complex working conditions and effectively solve the problem of "sticky bag".
[0004] A Chinese patent with publication number CN115970395A discloses a method for treating polyester filter material to make it waterproof and wear-resistant and the filter material prepared. The method prepares and uses a nano-silica aerogel / waterproof and oil-proof composite impregnation liquid to impregnate the polyester filter material, thereby achieving a simultaneous increase in the wear resistance and waterproof performance of the polyester filter material. The main focus of the patent may be on achieving a simultaneous improvement in the wear resistance and waterproof performance of the filter material, but ignores the attention to the oil resistance of the filter material and its long-term effectiveness at high temperatures.
[0005] The Chinese patent with publication number CN102392355A discloses a method for preparing water-repellent, oil-proof and easy-to-clean filter material, which uses PTFE emulsion and long-chain alkyl silicone oil to perform ordinary impregnation treatment on the filter material to achieve water-repellent and oil-proof properties. However, in actual industrial environments, the composition of dust is complex and diverse, containing sticky components, chemically active substances, etc. It is not comprehensive to rely solely on the water-repellent and oil-proof properties of PTFE emulsion to prevent bagging. The water-repellent and oil-proof properties of PTFE emulsion cannot effectively prevent the agglomeration and adhesion of dust, so bagging still occurs. Summary of the invention
[0006] The purpose of the present invention is to solve the above technical problems, provide a dust removal filter material with anti-condensation and self-cleaning properties and a preparation method thereof, and through specific surface treatment, effectively overcome the defects of the prior art, meet the needs of complex working conditions and solve the problem of "bag sticking".
[0007] In order to achieve the above technical purpose and meet the above technical requirements, the technical solution adopted by the present invention is: a dust removal filter material with anti-condensation and self-cleaning performance, the filter material is composed of a filter material body and a surface treatment layer; the filter material body is a filter felt prepared by a needle punching process; The surface treatment layer contains at least one component, which is a perfluoro and polyfluoroalkyl compound containing a straight chain of carbon atoms. The compound is evenly covered on the surface of the fiber layer, and the solid attachment amount of the compound on the filter material is 5 to 40 g / m 2 The surface treatment component evenly covers the fiber surface at a thickness of 0-50 microns, and covers at least 90% of the fiber surface area; at a thickness of 50-100 microns below the surface, the surface treatment component covers at least 75% of the fiber surface area; at a thickness of less than 200 microns below the surface, the surface treatment component covers less than or equal to 20% of the fiber surface area.
[0008] The perfluoro and polyfluoroalkyl compounds having a linear carbon atom chain in the surface treatment layer are preferably in the form of a linear chain of six or more carbon atoms.
[0009] The surface treatment layer also contains an organic fluorine-silicon modified acrylate compound, which is an antifouling and soft composite modifier with a solid attachment amount of 2 to 10 g / m 2 .
[0010] The surface treatment layer also contains an ethoxylated nonionic fluorocarbon surfactant, with a solid attachment amount of 1 to 3 g / m².
[0011] The main fibers constituting the filter material are preferably a mixture of one or more of PPS fibers, aramid fibers, glass fibers, basalt fibers, polyimide, polytetrafluoroethylene, and the like.
[0012] The method for preparing the above-mentioned dust removal filter material with anti-condensation and self-cleaning properties comprises the following steps: Step 1: Preparation of the filter material: Select the fiber and base fabric, open, mix, finely open, comb, lay the net, add the base fabric, and needle punch the short fibers to make a semi-finished needle felt. The unit weight is controlled at 400-900g / m 2 , the prepared filter felt is subjected to post-treatment by different methods such as singeing, calendering, heat setting, etc. according to the needs; Step 2: Preparation of surface coating treatment liquid, configured according to the mass of solid attachment on the filter surface: 5-40g / m² of straight-chain perfluoro and polyfluoroalkyl compounds of carbon atoms, 2-10g / m² of organic fluorine-silicon modified acrylate compounds, 1-3g / m² of ethoxylated non-ionic fluorocarbon surfactants. Some crosslinking agents and stabilizers can also be added to the configured treatment liquid, and the rest is water; Step 3: Surface coating spraying, evenly coating on the surface of the high temperature resistant fiber layer by spraying, the spraying distance during the spraying process is between 15cm-30cm, the spraying inclination angle is perpendicular to the filter material and the front and rear deflection is less than or equal to 45 degrees, the relative humidity is between 40% and 70%, and the ambient temperature is controlled between 10℃ and 35℃; Step 4: Dry and shape the prepared filter material to improve its performance stability; the drying and shaping temperature is preferably in three temperature ranges: Zone 1: 80°C ~ 120°C, treatment time is 1 to 2 minutes; Zone 2: 120°C ~ 160°C, treatment time is 1 to 2 minutes; Zone 3: 160°C ~ 220°C, treatment time is 5 to 10 minutes.
[0013] The crosslinking agent in the above step 2 is preferably a silane coupling agent, and the added content is 1-3%; the stabilizer is preferably one of butylated hydroxyanisole (BHA) or BHT (tert-butylhydroquinone), and the added content is 0.5-2%.
[0014] The dust removal filter material has anti-condensation and self-cleaning properties. The waterproof and oil-proof grades of the filter material are tested based on GB / T4745-2012 "Testing and Evaluation of Water-Repellent Properties of Textiles - Water-Repellent Method". The water-repellent grade of the filter material is above grade 4, and the oil-proof grade can reach above grade 7.
[0015] The dust removal filter material with anti-condensation and self-cleaning performance adopts VDI3926-1:2004 "Testing ofcleanable filter media - Standard test for the evaluation of cleanable filter media" to evaluate the filtering performance, and the dust removal rate can reach more than 99.99%.
[0016] Compared with the traditional structure, the invention has the following beneficial effects: 1. The surface treatment layer of the present invention realizes gradient coverage on the surface of the filter material, which can achieve higher levels of waterproof, oil-proof and anti-fouling performance, and can effectively improve the performance of the filter material under complex working conditions. In high temperature, high humidity or oil-containing environments, it has good comprehensive properties such as anti-condensation, self-cleaning, waterproof and oil-proof, and filtration, and can achieve long-term and stable maintenance of the anti-condensation and anti-adhesion capabilities of the filter bag material, effectively inhibiting the filter bag from sticking; 2. The filter material of the present invention has a water repellency level of above 4 and an oil repellency level of above 7. It can effectively reduce the outlet concentration, increase the circulation time, and the dust removal rate can reach above 99.99%. It has broad application prospects in industrial dust removal and civil fields. DETAILED DESCRIPTION
[0017] The present invention will be further described below.
[0018] A dust removal filter material with anti-condensation and self-cleaning properties, the filter material consisting of a filter material body and a surface treatment layer; the filter material body is a filter felt prepared by a needle punching process, and the unit gram weight is preferably 400-900g / m²; its fiber is preferably a mixture of one or more of PPS fiber, aramid fiber, glass fiber, basalt fiber, polyimide, polytetrafluoroethylene, etc.
[0019] Preparation method of dust removal filter material filter body: select suitable fibers (and base fabric), and process the short fibers through opening, mixing, fine opening, combing, web laying, base fabric addition, and needling to make semi-finished needle felt.
[0020] The surface treatment layer of the filter material contains at least one component, which is a perfluoro and polyfluoroalkyl compound containing a straight chain of carbon atoms, preferably in the form of a straight chain of six or more carbon atoms. The solid attachment amount of the compound on the filter material is preferably 5 to 40 g / m 2. Perfluoro and polyfluoroalkyl compounds with straight carbon atom chains can form a dense and stable protective film on the surface of the material, and their protective effect is significantly better than many ordinary waterproofing agents. Compared with ordinary waterproofing agents, the longer carbon chain makes the intermolecular forces stronger, the molecular arrangement is more compact, and the critical surface tension is lower. At the same time, the presence of fluorine atoms further enhances this effect. Fluorine atoms have strong electronegativity and can attract electrons, making the electron cloud around the molecules more densely distributed. This compact electron cloud structure increases the attraction between the molecular chains and forms a denser waterproof film. This film can not only effectively block the penetration of water molecules, but also repel oil molecules, making the material have excellent waterproof and oil-proof properties. However, when the number of carbon atoms is less than 6, the stability of its waterproof and oil-proof properties is greatly reduced. Experiments have shown that when the solid attachment amount of perfluoro and polyfluoroalkyl compounds with straight carbon atom chains on the filter material is 5 to 40 g / m², the compounds form a uniform gradient covering structure between the fiber layers. When the attachment amount is less than 5g / m², a complete protective film cannot be formed, and the compound cannot fully cover the fiber surface, resulting in the waterproof and oil-proof performance failing to meet the requirements of this case. When the attachment amount is higher than 40g / m², on the one hand, it will block the pores between the fibers, affecting the air permeability of the filter material, resulting in high pressure loss during filtration, resulting in reduced filtration performance and increased energy consumption; on the other hand, too much compound will cause accumulation on the material surface, forming an uneven coating, which will lead to poor stability of the protective effect.
[0021] Its gradient attachment structure is: the fiber surface at a thickness of 0-50 microns is evenly covered, and the surface treatment component covers at least 90% of the fiber surface area. This area is the part that is in direct contact with the external environment and is the first line of defense against water and oil penetration. If the area is less than 90%, water molecules and oil molecules can easily enter the interior of the material through these gaps. This will result in the material's waterproof and oil-proof performance failing to meet the requirements, and once liquid enters, it will also affect the material's internal structure, such as causing the fibers to stick together and dust to easily penetrate, and thus the filtration efficiency will also fail to meet the requirements; at a thickness of 50-100 microns below the surface, the surface treatment component covers at least 75% of the fiber surface area. Although this depth area is not directly in contact with the external environment, it is still affected by liquid penetration. If the coverage area is insufficient, due to the incompleteness of the protective layer, the liquid gradually penetrates into this area, resulting in the filtration performance failing to meet the requirements, resulting in an increase in the dust outlet concentration and an increase in the pressure loss; at a thickness of less than 200 microns below the surface, the surface treatment component covers an area less than or equal to 20% of the fiber surface. In this deeper area, the performance is mainly maintained by the material's own structure and the upper layer's protection. If the coverage area is too large, the internal microstructure of the material will be excessively changed, causing the pores between the fibers to be blocked, resulting in the material's air permeability and filtration performance failing to meet the requirements. Moreover, too many compounds in this area will increase the cost and weight of the material, which does not meet the requirements of practical applications.
[0022] The filter material surface also contains organic fluorine silicon modified acrylate compounds, and the solid adhesion amount on the fiber surface is preferably 2-10g / m². This organic fluorine silicon modified acrylate compound can produce a synergistic enhancement effect with the aforementioned perfluorinated and polyfluorinated alkyl compounds containing straight chains of carbon atoms (waterproofing agents). Waterproofing agents mainly focus on preventing the penetration of water and oil, while organic fluorine silicon modified acrylate compounds can further reduce the dust adhesion rate on the filter material surface, achieving the effect of easy dust cleaning and low adhesion, forming a complementary protection system. For example, when the waterproofing agent prevents the penetration of liquid, the organic fluorine-silicone modified acrylate compound can prevent dust and other solid dirt from being adsorbed on the fiber surface in a humid environment, thereby greatly improving the overall anti-fouling ability of the material. When the attachment amount of the organic fluorine-silicone modified acrylate compound is less than 2g / m², it cannot evenly cover the fiber surface, and the anti-fouling performance is not significantly improved. When the attachment amount of the organic fluorine-silicone modified acrylate compound is higher than 10g / m², excessive compounds accumulate on the fiber surface, destroying the original reasonable protective structure. While the cost increases, the anti-fouling effect will not be further improved, but the filtration efficiency will be reduced.
[0023] The surface of the filter material also contains an ethoxylated nonionic fluorocarbon surfactant, and the solid attachment amount on the fiber surface is preferably 1-3g / m². The surfactant can reduce the surface tension of the solution and change the interfacial properties between the solution and the material. The surfactant forms an adsorption layer on the fiber surface, so that some solute molecules are preferentially adsorbed in this layer. As the impregnation proceeds, due to the distribution gradient of the surfactant, the adsorption and diffusion of the solute also present a gradient change, thereby forming an impregnation layer with a higher concentration on the material surface, and the degree of impregnation gradually decreases toward the inside of the material, so that the coating produces a gradient stratification effect. This treatment effect makes the surface treatment layer evenly cover the fiber surface at a thickness of 0-50 microns on the surface, and covers at least 90% of the area of the fiber surface; at a thickness of 50-100 microns below the surface, the surface treatment component covers at least 75% of the area of the fiber surface; at a thickness of less than 200 microns below the surface, the surface treatment component covers less than or equal to 20% of the area of the fiber surface. When the attachment rate of ethoxylated nonionic fluorocarbon surfactant is less than 1g / m², due to the small amount of surfactant, a complete and effective adsorption layer cannot be formed on the fiber surface, which will lead to the surface tension of the solution cannot be fully reduced, the interface property change effect is not good, the adsorption of solute molecules becomes disordered and insufficient, and the ideal concentration gradient cannot be formed during the impregnation process, which makes it difficult for the coating to produce the expected gradient stratification effect, and the quality of the final product is reduced, such as uneven coating thickness, insufficient internal impregnation and other problems, affecting the performance of the filter material, such as reduced filtration efficiency and stability. When the attachment rate of ethoxylated nonionic fluorocarbon surfactant is greater than 3g / m², excessive surfactant will produce an overly thick adsorption layer on the fiber surface, which will cause the adsorption layer to be too viscous, solute molecules to aggregate excessively on the surface, block the surface channels, and hinder the normal diffusion of solutes into the material. Moreover, this overly thick adsorption layer will cause uneven stress distribution inside the coating, making the coating prone to cracking or peeling. At the same time, too much surfactant will also increase production costs and have an adverse effect on subsequent processing and other properties of the product, such as making the air permeability of the filter material worse or making it easier to adsorb impurities during actual use.
[0024] Preparation of surface coating treatment liquid for dust removal filter materials: Configure according to the mass of solid attachment on the filter material surface: 5~40g / m² of straight-chain perfluoro and polyfluoroalkyl compounds of carbon atoms, preferably 2~10g / m² of organic fluorine-silicon modified acrylate compounds, and preferably 1~3g / m² of ethoxylated nonionic fluorocarbon surfactants; silane coupling agent (added content is 1-3%), stabilizer BHA (butylated hydroxyanisole) or BHT (tert-butylhydroquinone) can also be added to the treatment liquid, and the added content is 0.5-2%, and the rest is water to prepare the surface coating treatment liquid. The addition of silane coupling agent is conducive to the uniform coverage of the coating on the fiber surface, which can adjust the rheological properties of the coating solution, promote the dispersion and distribution of each component, and help the coating produce a gradient stratification effect. At the same time, the siloxy group at one end can react with the hydroxyl group on the fiber surface to form a chemical bond, and the organic group at the other end can interact with the organic component of the coating, significantly enhancing the bonding strength between the coating and the fiber. When the addition amount is less than 1%, the interface between the inorganic components and the organic coating on the surface of the filter material cannot be fully covered, resulting in insufficient bonding between the coating and the filter material, thereby reducing the durability of the filter material. Because the amount of silane coupling agent is too small, it is impossible to form sufficient chemical bonds or physical adsorption to enhance the adhesion of the interface. When the addition amount is higher than 3%, the excess silane coupling agent will form agglomerates in the coating. These agglomerates will affect the uniformity of the coating, causing changes in the coating performance in local areas, reducing the air permeability of the coating, and increasing the pressure loss. In addition, too much silane coupling agent will also increase costs and reduce the cost performance of the product. Stabilizers BHA (butylated hydroxyanisole) or BHT (tert-butylhydroquinone) are mainly used to prevent the components in the coating from being oxidized during storage or use. If the addition amount is less than 0.5%, its antioxidant capacity is insufficient. In actual environments, coating materials will undergo oxidation reactions due to exposure to oxygen, ultraviolet rays and other factors, resulting in reduced coating performance, such as discoloration and embrittlement. When the addition amount exceeds 2%, on the one hand, it will have a negative impact on other properties of the coating, such as changing the chemical stability of the coating and causing adverse reactions with other components. On the other hand, too much stabilizer will also increase production costs and affect the physical properties of the coating to a certain extent, such as increasing the hardness of the coating and reducing its flexibility.
[0025] Spraying of surface coating of dust removal filter material: The treatment liquid is evenly coated on the surface of the high temperature resistant fiber layer by spraying. During the spraying process, the spraying distance is preferably between 15cm and 30cm, and the spraying angle is less than or equal to 45 degrees before and after the vertical filter material. The relative humidity is preferably between 40% and 70%, and the ambient temperature is preferably between 10℃ and 35℃. After a large number of experiments, it is known that when the above process parameters are selected, the coating can obtain the best gradient distribution effect. When the spraying distance is less than 15cm, the treatment liquid sprayed from the spray gun has a large impact force under high pressure and is not easy to disperse, which will cause the sprayed liquid to be too concentrated locally and unevenly distributed, and it is easy for the treatment liquid to penetrate deeper, and it is not easy for the emulsion to concentrate on the fiber surface, which will affect the uniformity and surface properties of the coating, such as surface flatness, glossiness, etc. Moreover, a too close distance will cause the coating to be too thick in some areas, and defects such as cracking will easily occur during the drying process, and it will also cause waste of treatment liquid. When the spraying distance is greater than 30cm, the treatment liquid will diffuse and drift before reaching the fiber surface, resulting in a reduction in the amount of treatment liquid effectively attached to the fiber layer, and the coating thickness is difficult to reach the expected standard, affecting the integrity and functionality of the coating, and failing to form a continuous, uniform and sufficiently thick protective coating, thereby reducing the filtration efficiency and service life of the dust removal filter material. When the spraying angle is greater than ±45 degrees, the coating direction of the treatment liquid on the fiber surface is too inclined, and most of the treatment liquid will drift into the surrounding environment and cannot be effectively coated on the fiber surface, and cannot be evenly attached to the fiber surface, resulting in uneven coating thickness, and some areas may have missing or too thin coatings, which in turn affects the overall performance of the dust removal filter material, such as reducing its interception effect and anti-pollution ability for dust and other particulate matter. Most of the treatment liquid will drift into the surrounding environment and cannot be effectively coated on the fiber surface, resulting in a large amount of treatment liquid waste and environmental pollution, and at the same time, it is completely impossible to achieve effective coating treatment of the fiber layer, so that the dust removal filter material cannot obtain the expected surface coating performance. When the relative humidity is lower than 40%, the environment is too dry, and the water in the treatment liquid evaporates quickly, causing the viscosity of the treatment liquid to change during the spraying process, becoming too thick, affecting its fluidity and atomization effect, making the spraying uneven, and easily forming granular or block accumulation on the fiber surface instead of a uniform coating, thereby affecting the coating quality and the filtering performance of the dust removal filter material. When the relative humidity is higher than 70%, the ambient humidity is high, and the evaporation rate of the water in the treatment liquid slows down, which will make the coating dry for too long. During the drying process, it is easy to absorb impurities and dust in the air, polluting the coating surface, and the high humidity environment will affect the chemical reaction activity of certain components in the treatment liquid, resulting in a decrease in the bonding strength between the coating and the fiber, and poor durability and stability of the coating.When the ambient temperature is lower than 10°C, the viscosity of the treatment liquid will increase and the fluidity will deteriorate, which is not conducive to atomization and uniform coating during the spraying process, resulting in uneven thickness and rough surface of the coating. At the same time, the low temperature environment will reduce the reactivity of some components in the treatment liquid, affecting the curing speed and quality of the coating, making the coating and the fiber bonded loose, and reducing the performance and service life of the dust removal filter material. When the ambient temperature is higher than 35°C, the solvent and other components in the treatment liquid evaporate too quickly, causing the concentration of the treatment liquid to change during the spraying process, affecting its uniformity and stability, and easily causing defects such as uneven coating surface and bubbles. In addition, the high temperature environment may cause some components in the treatment liquid to decompose or denature, destroy the structure and performance of the coating, and reduce the protective effect and reliability of the dust removal filter material.
[0026] Surface drying and shaping of dust removal filter materials: Dry and shape the prepared filter materials to improve their performance stability. In order to make the surface coating obtain a stable gradient structure, the drying and shaping temperature is preferably in three intervals: Zone 1: 80℃ - 120℃, the treatment time is 1-2 minutes. This stage is mainly to allow the waterproof agent to be evenly distributed in the filter material, so that the excess water in the system can evaporate. The lower temperature can prevent the coating from evaporating quickly and accumulating on the surface of the material, so that it can fully penetrate between the fibers inside the material; Zone 2: 120℃ - 160℃, the treatment time is 1-2 minutes, the surface coating begins to solidify initially, and the water continues to evaporate. As the temperature rises, some components in the reagent will undergo a chemical reaction, causing it to gradually change from liquid to solid, and better adhere to the fiber surface of the material; Zone 3: 160℃ - 220℃, the treatment time is 5-10 minutes, which is the key stage of drying and shaping. In this high temperature stage, the coating is completely cured to form a more stable and dense waterproof structure. The high temperature can promote the chemical bonds in the waterproof agent to fully react, so that it can be closely combined with the fibers of the filter material.
[0027] Various performance testing methods of the filter material of the present invention are as follows, but are not limited to these testing methods.
[0028] Test method for the surface adhesion ratio of dust removal filter materials: The adhesion of fiber surface coating is analyzed by combining SEM, UV-Vis spectroscopy (UV-Vis) and Raman spectroscopy technology on fibers in different parts.
[0029] Dust removal filter material surface water and oil resistance test: Based on GB / T4745-2012 "Testing and Evaluation of Water Resistance of Textiles - Water Dipping Method", the filter material's water resistance and oil resistance levels are tested to evaluate its water and oil resistance performance.
[0030] Water repellency: Take a flat filter material of at least 18*18cm, and clamp it on a fixture (the fixture is at a 45° angle to the horizontal plane) after humidification. With the front side facing up, pour 250ml of water into the funnel quickly and steadily, and continue spraying for 25~30s; after stopping the spraying, remove the holder with the sample, tap it once against a solid hard object with the front side facing down, and then rotate 180° and tap it again; finally, evaluate it according to the water-repellent rating. For this case: the water repellency is qualified if it is greater than or equal to level 4.
[0031] Oil repellency: Spread the surface of the test sample on a smooth horizontal absorbent pad with the front side facing up, and drop 5 small drops of oil No. 1 on the test sample (volume about 0.05ml), with a dropper mouth 6mm away from the sample surface, observe the droplets at a 45° angle for 30s±2s, and evaluate according to the evaluation criteria and comparison chart. For this case: the oil repellency is qualified if it is greater than or equal to level 7.
[0032] Evaluation of the surface filtration performance of dust removal filter materials: The filtration performance of the filter materials is evaluated using VDI3926-1:2004 "Testing of cleanable filter media - Standard test for the evaluation of cleanable filter media" to determine their filtration effect and efficiency in actual dust removal applications.
[0033] The performance of the filter material is determined based on the VDI3926 standard. The size of the test sample is 150 mm in diameter and the dust concentration fed is 5.0 ± 0.5 g / m 3 , the filtration wind speed is 2m / min (air volume 1.85m 3 / h). The experimental sequence is the initial 30 times + stabilization 5000 times + the final 30 times. The method for the initial 30 times and the final 30 times is: as the running time increases, the pressure difference on both sides of the filter material will gradually increase. When the pressure difference reaches 1000Pa, the pulse air cleans the dust on the surface of the filter material, and then proceeds to the next process. The process is repeated 30 times. During the experiment, the experimental time (t / s) and pressure changes are recorded, and the weight M (g) of the dust passing through the filter material is weighed. The stabilization process refers to the process of cleaning the filter material at a time interval of 5s during operation, the cleaning pressure is 5bar, and the number of cleaning times is 5000. The calculation formula for the outlet dust concentration and capture efficiency is as follows: The outlet dust concentration C = the weight of dust passing through the filter material M / (1.85×time t / 3600), the unit of the outlet dust concentration C is g / m 3 ; Collection efficiency = (1-export dust concentration C / 5) × 100%; The pressure loss is the pressure loss automatically recorded by the equipment after the last injection of the last 30 times; The cycle time is the total time spent on the last 30 cycles.
[0034] The present invention is further described in detail below through specific examples and comparative examples, but the present invention is not limited to these examples.
[0035] Example 1: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of the surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 8g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0036] Example 2: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0037] Example 3: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 35g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0038] Example 4: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, six carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0039] Example 5: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 3g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0040] Example 6: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 9g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0041] Example 7: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 15g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100°C for 1.5 minutes, the temperature of the second zone is 140°C for 1.5 minutes, and the temperature of the third zone is 180°C for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0042] Example 8: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 1.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0043] Example 9: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, organic fluorine silicon modified acrylate compounds have a surface solid content of 5g, ethoxy non-ionic fluorocarbon surfactants have a surface solid content of 2g, silane coupling agent content is 2.5%, BHT (tert-butyl hydroquinone) content is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100°C for 1.5 minutes, the temperature of the second zone is 140°C for 1.5 minutes, and the temperature of the third zone is 180°C for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0044] Example 10: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, organic fluorine silicon modified acrylate compounds have a surface solid content of 5g, ethoxy nonionic fluorocarbon surfactants have a surface solid content of 5g, silane coupling agent content is 2.5%, BHT (tert-butyl hydroquinone) content is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100°C for 1.5 minutes, the temperature of the second zone is 140°C for 1.5 minutes, and the temperature of the third zone is 180°C for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0045] Example 11: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of the surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 1.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100°C for 1.5 minutes, the temperature of the second zone is 140°C for 1.5 minutes, and the temperature of the third zone is 180°C for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0046] Example 12: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100°C for 1.5 minutes, the temperature of the second zone is 140°C for 1.5 minutes, and the temperature of the third zone is 180°C for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0047] Example 13: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0048] Example 14: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of the surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxy non-ionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHA (butylated hydroxyanisole) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100°C for 1.5 minutes, the temperature of the second zone is 140°C for 1.5 minutes, and the temperature of the third zone is 180°C for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0049] Example 15: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 8g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxy non-ionic fluorocarbon surfactant is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0050] Example 16: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 8g, organic fluorine silicon modified acrylate compounds have a surface solid content of 5g, ethoxy non-ionic fluorocarbon surfactants have a surface solid content of 2.5g, silane coupling agent content is 2.5%, BHT (tert-butyl hydroquinone) content is 1%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the first zone temperature is 100°C for 1.5 minutes, the second zone temperature is 140°C for 1.5 minutes, and the third zone temperature is 180°C for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 1.
[0051] Comparative Example 1: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of the surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 1g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 2.
[0052] Comparative Example 2: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 3g, organic fluorine silicon modified acrylate compounds have a surface solid content of 5g, ethoxy non-ionic fluorocarbon surfactants have a surface solid content of 2.5g, silane coupling agent content is 2.5%, BHT (tert-butyl hydroquinone) content is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the first zone temperature is 100℃ for 1.5 minutes, the second zone temperature is 140℃ for 1.5 minutes, and the third zone temperature is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 2.
[0053] Comparative Example 3: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 45g, the surface solid content of organic fluorine silicon modified acrylate compounds is 0.5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 2.
[0054] Comparative Example 4: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 60g, the surface solid content of organic fluorine silicon modified acrylate compounds is 15g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 2.
[0055] Comparative Example 5: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 8g, the surface solid content of organic fluorine silicon modified acrylate compounds is 0.5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 2.
[0056] Comparative Example 6: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 20g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 2.
[0057] Comparative Example 7: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 10g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 2.
[0058] Comparative Example 8: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 10%, the content of BHT (tert-butyl hydroquinone) is 1.5%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 2.
[0059] Comparative Example 9: A mixture of aramid fibers is selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² is made through processes such as opening and mixing, and then heat-setting treatment is performed. In the preparation of surface coating treatment, eight carbon atom straight-chain perfluoro and polyfluoroalkyl compounds are taken to make their surface solid content 25g, the surface solid content of organic fluorine silicon modified acrylate compounds is 5g, the surface solid content of ethoxylated nonionic fluorocarbon surfactants is 2.5g, the content of silane coupling agent is 2.5%, the content of BHT (tert-butyl hydroquinone) is 10%, and the rest is water. Spraying is performed according to the specified spraying parameters, and then in the drying and setting equipment, the temperature of the first zone is 100℃ for 1.5 minutes, the temperature of the second zone is 140℃ for 1.5 minutes, and the temperature of the third zone is 180℃ for 8 minutes. Finally, the filter material of the present invention is obtained. The physical properties of the filter material are shown in Table 2.
[0060] Comparative Example 10: A mixture of aramid fibers was selected as the main fiber of the filter material, and a semi-finished needle felt with a unit weight of 600 g / m² was made through processes such as opening and mixing, and then heat-set. The first zone was treated at 100°C for 1.5 minutes, the second zone was treated at 140°C for 1.5 minutes, and the third zone was treated at 180°C for 8 minutes. Finally, the filter material of the present invention was obtained. The physical properties of the filter material are shown in Table 2.
[0061] Table 1 Physical properties of Examples 1-16
[0062] Table 2 Physical properties of Comparative Examples 1-10
[0063] According to the above table, we can draw the following conclusions: (1) The data of Examples 1-6 fully illustrate that within the specified range, the water resistance is 4 and the oil resistance is 7 or above, and the performance indicators of the obtained filter material all meet the requirements of the present invention. After high temperature treatment at 240°C for 24h, the filter material still maintains a water resistance of 3~4 and an oil resistance of 6 or above.
[0064] (2) It can be seen from Examples 1, 2, and 3 that, under the same conditions, when the ratio of straight-chain perfluoro and polyfluoroalkyl compounds of carbon atoms is within the preferred range, the higher the attachment ratio, the higher the attachment ratio of the gradient distribution of surface coating thickness, and the higher the water and oil repellency level.
[0065] (3) As can be seen from Examples 2 and 4, when the carbon number of the straight-chain perfluoro and polyfluoroalkyl compounds is within the preferred range, the water and oil repellency level is higher when the carbon number is 8.
[0066] (4) It can be seen from Examples 2, 5, 6, and 7 that the attachment weight of the organic fluorine-silicon modified acrylic ester compound is within the preferred range. The higher the attachment weight, the lower the VDI outlet concentration of the obtained filter material and the longer the cycle time. When the addition ratio is too high, the dust removal ability becomes poor, the dust outlet concentration increases, the cycle time decreases, and the VDI performance index is poor.
[0067] (5) It can be seen from Examples 2, 8, 9 and 10 that, within the specified range, when different proportions of ethoxylated nonionic fluorocarbon surfactants are added, the performance indicators of the filter materials obtained meet the requirements of the present invention. When the addition ratio is too high, the dust removal capacity deteriorates, the dust outlet concentration increases, the cycle time decreases, and the VDI performance index is poor.
[0068] (6) It can be seen from Examples 2, 11, 12, and 13 that, within the specified range, when the silane coupling agent is added in different proportions, the performance indicators of the filter material obtained are all good. When the addition ratio is too high, the dust removal ability deteriorates, the dust outlet concentration increases, the cycle time decreases, and the VDI performance index is poor.
[0069] (7) It can be seen from Examples 2 and 14 that, within the specified range, when BHA (butylated hydroxyanisole) and BHT (tert-butylhydroquinone) are selected, the performance indicators of the obtained filter material are all good.
[0070] (8) It can be seen from Examples 2, 15, and 16 that within the specified range, when the stabilizer is added in different proportions, the performance indicators of the filter material obtained are all good. When the addition ratio is too high, the dust removal ability deteriorates, the dust outlet concentration increases, the cycle time decreases, and the VDI performance index is poor.
[0071] (9) It can be seen from Example 2 and Comparative Examples 1 and 2 that the attached gram weight of the straight-chain carbon atom perfluoro and polyfluoroalkyl compounds is too low. Although the waterproof and oil-proof performance meets the requirements of the present invention, the dust removal ability is deteriorated, the dust outlet concentration is increased, and the VDI performance index is poor.
[0072] (10) It can be seen from Example 2 and Comparative Examples 1 and 2 that the attachment weight of the straight-chain perfluoro and polyfluoroalkyl compounds of carbon atoms is too low, the attachment ratio of the gradient distribution of the surface coating at different thicknesses does not meet the requirements, the ability of the water and oil repellent is affected, the dust removal ability is deteriorated, the dust outlet concentration is increased, the cycle time is reduced, and the VDI performance index is poor.
[0073] (11) It can be seen from Example 2 and Comparative Examples 3 and 4 that the weight of the organic fluorine-silicon modified acrylate compound is too high, the adhesion ratio of the surface coating with different thickness gradient distribution is too high in some thickness ranges, the dust removal ability becomes poor, the dust outlet concentration increases, the cycle time decreases, and the VDI performance index is poor.
[0074] (12) It can be seen from Example 1 and Comparative Example 5 that the adhesion weight of the organic fluorine-silicone modified acrylate compound is too low, the adhesion ratio of the surface coating with different thickness gradient distribution does not meet the requirements in some thickness ranges, the ability of the water- and oil-repellent agent is affected, the dust removal ability becomes worse, the dust outlet concentration increases, and the VDI performance index is poor.
[0075] (13) It can be seen from Example 2 and Comparative Example 6 that if the adhesion weight of the organic fluorine-silicon modified acrylate compound is too high, the adhesion ratio of the surface coating with different thickness gradient distribution will not meet the requirements in some thickness ranges, the dust removal ability will be deteriorated, the dust outlet concentration will increase, and the VDI performance index will be poor.
[0076] (14) It can be seen from Example 2 and Comparative Examples 6, 7, 8 and 9 that if the ethoxylated nonionic fluorocarbon surfactant, silane coupling agent and stabilizer have too high an attachment weight, the attachment ratio of the surface coating with different thickness gradient distribution will not meet the requirements in some thickness ranges, the water and oil repellent capability will be affected, the dust removal capability will be deteriorated, the dust outlet concentration will be increased, and the VDI performance index will be poor.
[0077] (15) It can be seen from Example 4 and Comparative Example 10 that the dust removal filter material with anti-condensation and self-cleaning properties of the present invention has better water and oil repellency after treatment at 240°C for 24 hours, compared with the filter material using the same filter material as the main body and only adding perfluoro and polyfluoroalkyl compounds with straight carbon atoms. The VDI performance outlet concentration of the filter material of the present invention is 0.2-0.4 mg / m 3 , the outlet concentration is also slightly reduced, and the VDI performance index is better.
[0078] It can be seen from the above embodiments that the dust removal filter material with anti-condensation and self-cleaning performance of the present invention and its preparation method can effectively improve the performance of the filter material under complex working conditions, and has good comprehensive performance such as anti-condensation, self-cleaning, waterproof and oil-proof and filtering, and has broad application prospects in the field of industrial dust removal. The material ideas and methods of the present invention have a wide range of applications, not limited to industrial dust removal, and can also be expanded to other fields such as civilian clothing, building protection, agricultural production, etc. in the future. It has significant advantages and feasibility of expanding and extending to multiple fields and deeply integrating applications.
[0079] The above embodiments of the present invention are merely examples to clearly illustrate the present invention, but are not intended to limit the protection scope of the present invention. All equivalent technical solutions also belong to the scope of the present invention. The patent protection scope of the present invention should be defined by the claims.
Claims
1. Dust removal filter material with anti-condensation and self-cleaning properties, characterized by: The filter material consists of a filter material body and a surface treatment layer; the filter material body is a filter felt prepared by a needle punching process, and the surface treatment layer contains at least one component, which is a perfluoro and polyfluoroalkyl compound containing a straight chain of carbon atoms, and the compound is evenly covered on the surface of the fiber layer, and the solid attachment amount of the compound on the filter material is 5 to 40 g / m²; the surface treatment component evenly covers the fiber surface at a thickness of 0-50 microns on the surface, and covers at least 90% of the area of the fiber surface; at a thickness of 50-100 microns below the surface, the surface treatment component covers at least 75% of the area of the fiber surface; at a thickness of less than 200 microns below the surface, the surface treatment component covers an area less than or equal to 20% of the fiber surface.
2. The dust removal filter material with anti-condensation and self-cleaning properties according to claim 1, characterized in that: The perfluoro and polyfluoroalkyl compounds having a linear carbon atom chain in the surface treatment layer are preferably in the form of a linear chain of six or more carbon atoms.
3. The dust removal filter material with anti-condensation and self-cleaning properties according to claim 1, characterized in that: The surface treatment layer also contains organic fluorine-silicon modified acrylate compounds, and the solid adhesion amount is 2 to 10 g / m 2 .
4. The dust removal filter material with anti-condensation and self-cleaning properties according to claim 1, characterized in that: The surface treatment layer also contains ethoxylated nonionic fluorocarbon surfactants with a solid attachment amount of 1 to 3 g / m².
5. The dust removal filter material with anti-condensation and self-cleaning properties according to claim 1, characterized in that: The fiber constituting the main body of the filter material is a mixture of one or more of PPS fiber, aramid fiber, glass fiber, basalt fiber, polyimide and polytetrafluoroethylene.
6. A method for preparing a dust removal filter material having anti-condensation and self-cleaning properties as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Preparation of the filter material: Select the fiber and base fabric, open, mix, finely open, comb, lay the net, add the base fabric, and needle punch the short fibers to make a semi-finished needle felt. The unit weight is controlled at 400-900g / m 2 , subjecting the prepared filter felt to post-treatments such as singeing, calendering and heat setting as required; Step 2: Preparation of surface coating treatment liquid, configured according to the mass of solid attachment on the filter surface: 5-40g / m² of straight-chain perfluoro and polyfluoroalkyl compounds of carbon atoms, 2-10g / m² of organic fluorine-silicon modified acrylate compounds, 1-3g / m² of ethoxylated non-ionic fluorocarbon surfactants, and crosslinking agents and stabilizers can also be added to the configured treatment liquid, and the rest is water; Step 3: Surface coating spraying, evenly coating on the surface of the high temperature resistant fiber layer by spraying, the spraying distance during the spraying process is between 15cm-30cm, the spraying inclination angle is perpendicular to the filter material and the front and rear deflection is less than or equal to 45 degrees, the relative humidity is between 40% and 70%, and the ambient temperature is controlled between 10℃ and 35℃; Step 4: Dry and shape the prepared filter material to improve its performance stability; the drying and shaping temperature is in three temperature ranges: Zone 1: 80°C to 120°C, and the treatment time is 1 to 2 minutes; Zone 2: 120℃~160℃, treatment time is 1~2 minutes; Zone 3: 160℃~220℃, treatment time is 5~10 minutes.
7. The method for preparing the dust removal filter material with anti-condensation and self-cleaning properties according to claim 6, characterized in that: The crosslinking agent in step 2 is preferably a silane coupling agent, and the added content is 1-3%; the stabilizer is preferably one of butylated hydroxyanisole (BHA) or BHT (tert-butylhydroquinone), and the added content is 0.5-2%.
8. The dust removal filter material with anti-condensation and self-cleaning properties according to claim 1, characterized in that: The waterproof and oil-proof grades of the filter material are tested based on GB / T4745-2012. The water-repellent grade of the filter material is above grade 4, and the oil-proof grade is above grade 7.
9. The dust removal filter material with anti-condensation and self-cleaning properties according to claim 1, characterized in that: The filtration performance of the filtration material is evaluated by testing using VDI3926-1:2004, and the dust removal rate is above 99.99%.
Citation Information
Patent Citations
Waterproof and wear-resistant treatment method for polyester filter material and prepared filter material
CN115970395A
Preparation method of high-temperature-resistant filtering material with high filtering efficiency
CN101829453A
Preparation method for water-repelling grease-proofing easy-ash-removal filter material
CN102392355A
Filter media, elements, and methods
CN109562311A
Polytetrafluoroethylene membrane filter material with hydrophobic and oil-repellent functions and preparation method of polytetrafluoroethylene membrane filter material
CN114130122A
Cited By
Composite high-temperature-resistant filter cloth and preparation method thereof
CN120789783A